2020
DOI: 10.3390/pathogens9060489
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Incorporation of Helicobacter pylori into Candida albicans Caused by Acidic pH Stress

Abstract: Yeasts can adapt to a wide range of pH fluctuations (2 to 10), while Helicobacter pylori, a facultative intracellular bacterium, can adapt to a range from pH 6 to 8. This work analyzed if H. pylori J99 can protect itself from acidic pH by entering into Candida albicans ATCC 90028. Growth curves were determined for H. pylori and C. albicans at pH 3, 4, and 7. Both microorganisms were co-incubated at the same pH values, and the presence of intra-yeast bacteria was evaluated. Intra-yeast bacteria-like bodies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…It must be emphasized that, among the bacterial profiles found in our vaginal discharge samples, a high percentage (32%) corresponded to the genotype cagA+ , vacAs1a/m1 , dupA− , which, in accordance with the literature, is associated to cases of gastric cancer [ 32 , 33 , 61 ]. It was also detected that the amplification of vacA gene regions provided results not described in previous studies [ 31 , 33 ] including strains which did not amplified any of the alleles codifying the medial region ( m1 y m2 ), while others did not amplify the signal region ( s1a , s1b or s2 ). To the best of our knowledge, there is no scientific literature explaining the causes which can influence this phenomenon in H. pylori .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…It must be emphasized that, among the bacterial profiles found in our vaginal discharge samples, a high percentage (32%) corresponded to the genotype cagA+ , vacAs1a/m1 , dupA− , which, in accordance with the literature, is associated to cases of gastric cancer [ 32 , 33 , 61 ]. It was also detected that the amplification of vacA gene regions provided results not described in previous studies [ 31 , 33 ] including strains which did not amplified any of the alleles codifying the medial region ( m1 y m2 ), while others did not amplify the signal region ( s1a , s1b or s2 ). To the best of our knowledge, there is no scientific literature explaining the causes which can influence this phenomenon in H. pylori .…”
Section: Discussionsupporting
confidence: 86%
“…These results are comparable to those reported by Siavoshi et al, (2013) [ 30 ], who indicated that C. albicans was the vaginal yeast in which intracellular H. pylori was most frequently found (80%) but they did not identify Candida not albicans [ 30 ]. These results, altogether with the report of Sanchez-Alonzo et al (2020) [ 33 ], in which it was demonstrated that H. pylori under pH stressing conditions harbors within C. albicans , support the hypothesis that yeasts belonging to the genus Candida can be included among the yeasts capable of protecting or serving as a vehicle for H. pylori [ 33 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Recently, our research group demonstrated that acidic pH, as a stress factor, induces the entry of H. pylori into Candida albicans cells, where the bacterium may find a shelter against unfavorable pH conditions within the yeast cells [ 24 ], a yeast that colonizes the gastrointestinal tract of nearly 40% of healthy humans [ 25 , 26 ]. Similarly, certain antibiotics may also trigger the harboring of H. pylori within C. albicans; therefore, the H. pylori and C. albicans interaction may be an example of the bacteria–yeast relationship, which may cause the failure of anti- H. pylori treatments.…”
Section: Introductionmentioning
confidence: 99%